A comprehensive study and performance based evaluation on routing protocols of WiMAX - Shabnam, Farzana; Saha, Aparna; Sobhan, Rifat Binte; Debnath, Tanmoy (© 2016 IEEE, 2018)
This conference paper was published in the International Conference on Innovations in Science, Engineering and Technology, ICISET 2016; Dhaka; Bangladesh; 28 October 2016 through 29 October 2016 [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/ICISET.2016.7856533 The Journal's website is at: https://ieeexplore.ieee.org/document/7856533/